The NeuroWES project: lessons learned from comprehensive phenotyping and genetic analysis of neurodevelopmental disorders over a decade - Simona Cardaropoli; Lisa Pavinato; Slavica Trajkova; Diana Carli; Verdiana Pullano; Flavia Palermo; Alessandro Mussa; Elisa Biamino; Vincenzo Antona; Andrea Zonta; Paola Dimartino; Mariia Zadorozhna; et al. (Human Genetics, 2026)
Exome sequencing (ES) has become a primary tool for diagnosing neurodevelopmental disorders (NDDs), yet the interpretation of genetic variants in large, heterogeneous cohorts presents significant challenges that automated pipelines often fail to resolve. This study showcases the complexities and novel findings derived from a decade-long analysis of 419 Italian NDD patient-parent trios. While ES established a molecular diagnosis in 36.5% of cases (53.8% in syndromic presentations), our investigation moves beyond diagnostic yield to highlight the critical value of manual curation integrated with deep phenotyping. We demonstrate how this rigorous approach uncovers complex disease mechanisms, revealing that variants initially misclassified as missense or stop-gain are, in fact, pathogenic splicing defects confirmed by functional analysis. Furthermore, we resolve the paradox of pathogenic truncating PPM1D variants in control databases by demonstrating their somatic mosaic nature, a crucial insight for population data interpretation. Our work also refines gene-disease correlations by challenging the established role of MID2 in NDDs, providing further evidence for DSCAM as a high-confidence risk gene, and expanding the known phenotypic spectrum of disorders, such as a novel GNAI2 -related syndrome lacking expected immune dysfunction. This study underscores that navigating the complexities of large NDD cohorts requires a detailed, expert-driven approach to not only enhance diagnostic yield but also to advance our fundamental understanding of rare disease genetics.